Islamic Family Law and the Challenges of Divorce in the Modern Era: A Legal and Socio-Religious Review - Abdul Kahar Syarifuddin (AIQU: Journal Multidiscipliner of Science, 2025)
This study examines Islamic Family Law and the challenges of divorce in the modern era through a literature review approach. Divorce in contemporary Muslim society is no longer shaped solely by traditional domestic problems, but also by broader social transformation, including economic pressure, changing gender roles, technological development, weakening interpersonal communication, and shifting religious and cultural values. These conditions make divorce not only a legal matter but also a socio-religious issue that requires a comprehensive and contextual analysis. This study aims to analyze the concept of divorce in Islamic family fiqh, identify the legal and socio-religious factors influencing divorce in the modern era, and explore the relevance of Islamic family law in responding to contemporary family problems. This research employs library research with a qualitative-descriptive approach. Data were collected from primary and secondary sources, including books, classical Islamic texts, journal articles, previous studies, and relevant legal documents. The data were analyzed using content analysis through data reduction, thematic categorization, interpretation, and conclusion drawing. The findings show that divorce in Islamic family fiqh is legally permissible but ethically restricted, and it is positioned as a last resort after reconciliation efforts fail. The study also finds that many modern divorce cases are influenced by social change, limited religious literacy, emotional immaturity, and misunderstandings of rights and obligations within marriage. By relating Islamic family fiqh to theories of family law and maqāṣid al-sharī‘ah, this study concludes that family fiqh remains highly relevant, provided that it is interpreted contextually and implemented in ways that promote justice, welfare, mediation, and family resilience in contemporary Muslim society.